Validating the Impact of FIRST Framework for Teachers Professional Development (Proceedings of the International Conference on Education, 2020)
Teachers’ Professional Development has always been an area of growing interest and constant research. Several educational researchers and authors have thoroughly explored the Teachers’ professional development domain with the efforts to develop and train teachers on how to understand, experience, practice and have a sustainable impact on learners. This paper attempts to explore the impact of FIRST Framework on Teacher Professional Development, teachers experience as learners and teachers motivation to transfer their learning into performance in the classrooms using case study methodology. FRIST Framework is designed on the basis of educational psychology, neuroscience, and cognitive psychology, to create a framework that promotes Active Deep Learning and inspires a positive transformation in mindset and behaviors. Major findings: (1) Teachers reported that FIRST Framework is comprehensive and compiles various educational theories, models and strategies, (2) Teachers were able to apply the principles and strategies in their classrooms directly and immediately after the professional program days were over, (3) Student’s feedback and overall experience were enhanced. Keywords- Active Learning; Deep Learning; Facilitation; Student Experience; Teachers Professional Development, 21st Century Learning, Active Deep Learning, Learner eXperience Facilitation
Keywords: Active Learning; Deep Learning; Learner eXperience Facilitation; Active Deep Learning; 21st Century Learning; Student Experience; Facilitation; Teachers Professional Development